The Analyzing miR-106b-5p and miR-93-5p as Promising Diagnostic Markers for Autism Spectrum Disorder: NA - Safdar, Ayesha; Khurshid, Sobia; Farwa, Umme; Bakhtiar, Syeda Marriam (Current Trends in OMICS, 2021)
Autism spectrum disorder (ASD) is a complex group of neurodevelopmental disorders encompassing perturbations in verbal and non-verbal communication, social skills, as well as repetitive and restricted behaviour, activity, or response. The pathogenesis of the disorder is still unknown, yet several studies have documented the involvement of both genetic and environmental factors in its onset. Intense efforts have been made to identify reliable biomarkers to aid in early diagnosis. MicroRNAs (miRNAs) are the regulatory noncoding regions of ribonucleic acid (RNA) that can alter the expression of a gene through posttranscriptional mechanisms. In this study, an in-silico technique was used to identify two novel biomarkers, namely miR-106b-5p and miR-93-5p. The analysis identified that these diagnostic biomarkers are associated with ASD and can aid in its early treatment since miRNAs play a significant role in the development and function of the central nervous system (CNS).